Patentes e innovación social en las Universidades Públicas Estatales de México - Elisa Calderón-Altamirano; Eva Grissel Castro Coria; Liliana Getzali Pérez-Munguía (GECONTEC: Revista Internacional de Gestión del Conocimiento y la Tecnología, 2025)
The transfer of technology from universities to society has acquired a strategic role in promoting economic and social development, particularly following the enactment of the Bayh-Dole Act in the United States, which enabled universities to protect and commercialize intellectual property funded with public resources. In Mexico, State Public Universities (SPUs) possess the autonomy to define their own academic trajectories, allowing them to align their core functions with the social needs of the regions where they operate. This research aims to identify the necessary and/or sufficient conditions that foster technology transfer processes with significant social impact (TTPSI) within SPUs. To this end, the study employs Qualitative Comparative Analysis (QCA), a methodological approach suitable for determining the conditions that enable these transfer processes to succeed. The results reveal that university social responsibility (USR) emerges as the only necessary condition to explain TTPSI. In contrast, the conditions related to innovative development capabilities (IDC), engagement capabilities (EC), and institutional capabilities (IC) fail to meet the consistency criterion as necessary conditions. These findings underscore the relevance of designing institutional policies that focus on social impact, beyond the mere number of patents generated or agreements signed with the productive sector.